Reading Sociocultural Contexts Through Photographs: a Case Study of Women Photographs, Taken in the Early Republic Period of İzmir - Yurt, Canberk; Yurt, Canberk; Türkmen, Doruk; Günduru, Beliz; Destici, Orkun; Aşıcı, Burçin (My University, 2020)
The individuals reflect the socio-cultural, economic and political changes in their society with their appearances, like a mirror. From the late Ottoman period, through the declaration of the Republic, several modernization steps have taken place in Turkish society. During that period, photography has taken a crucial role in society, both as a profession and social innovation instrument, by being a representative of the societal changes. Through that, regulations such as Dress Reform and Women’s Suffrage Code, and western fashion have influenced women’s image and re-defined their roles in modern Turkish society. These reforms provided more self-confıdence and freedom to modern Turkish women. By that, the way women express themselves via photographs has been changed. This study aims to analyze the socio-cultural contexts, from the perspective of five randomly selected women photographs from İpek Cabadak’s private collection, which is named “Photographs Entrusted to the Future”. As a research method, iconographic visual analysis has been conducted, by considering social, historical and cultural incidents at that era, with the guidance of İpek Cabadak. Visual analysis of the selected photographs has been made based on some fashion clues, pre-iconographic data and historical facts from the early republic period. The analysis provides useful information about the roles and positions of Turkish women, their interactions and positionings among the society, in order to define the time and place those photographs have been taken and links between socio-cultural incidents. According to this study, photography can be considered a beneficial and efficient tool for visual analysis in historic socio-cultural studies.

Bireyler, dış görünüşleri aracılığıyla, bulundukları dönemin sosyokültürel, ekonomik ve politik değişimlerini yansıtırlar. Geç Osmanlı Dönemi’nden Cumhuriyet’in ilanına kadar geçen sürede, Türk toplumunda bir dizi modernleşme adımları atılmıştır. Bu süreçte fotoğraf, hem mesleki bir enstrüman hem de yenileşimci bir araç olarak sosyal değişimleri temsil etmesinden dolayı, toplumda kritik bir role sahip olmuştur. Bunun yanı sıra, Kıyafet Reformu ve kadınlara seçme-seçilme hakkının tanınması gibi regülasyonlar ve batı modası, kadın imajına ilham vermiş ve kadınların Türk toplumundaki rolünün yeniden tanımlanmasını sağlamıştır. Bu reformlar kadınlara daha fazla özgüven ve özgürlük sağlamıştır. Bununla birlikte kadınların fotoğraflarda kendini ifade etme şekli değişmiştir. Bu çalışma, İpek Cabadak’ın “Geleceğe Emanet Fotoğraflar” isimli özel fotoğraf koleksiyonundan rastgele seçilen beş kadın fotoğrafının sosyokültürel bağlamda analiz edilmesini hedeflemektedir. Araştırma yöntemi olarak seçilen ikonografik görsel analiz metodu, dönemin sosyal, tarihi ve kültürel olayları doğrultusunda ve İpek Cabadak’ın yol göstericiliği ile uygulanmıştır. Seçilen fotoğraflarda erken Cumhuriyet döneminin moda ipuçlarına, pre-ikonografik veriye ve tarihi gerçekliklere dayalı ikonografik görsel analizler yapılmıştır. Bu analizle, fotoğrafların çekildiği zaman ve mekanlar ile sosyo-kültürel olaylarla ilişkisini tanımlamak amacıyla, Türk kadını, Türk kadınının toplumdaki etkileşimi ve konumu gibi konular hakkında kullanılabilir bilgiler elde edilmiştir. Bu çalışma doğrultusunda, fotoğrafın, tarihsel sosyokültürel çalışmalarda yapılan görsel analizlerde faydalı ve etkili bir araç olduğu sonucuna varılmıştır.
Fotoğraflar Yoluyla Sosyokültürel Bağlamların Okunması; İzmir’in Erken Cumhuriyet Döneminde Çekilen Kadın Fotoğrafları Vaka Çalışması
Keywords: Photography; Women studies; Visual analysis